Word Level Stress and Lexical Processing in 17‐Month‐Old Infants. (9th October 2018) - Campbell, Jennifer; Graham, Susan; Curtin, Suzanne
Abstract : Detailed representations enable infants to distinguish words from one another and more easily recognize new words. We examined whether 17‐month‐old infants encode word stress in their familiar word representations. In Experiment 1, infants were presented with pairs of familiar objects while hearing a target label either properly pronounced with the correct stress (e.g., baby /'beɪbi/) or mis‐pronounced with the incorrect stress pattern (e.g., baby /beɪ'bi/). Infants mapped both the correctly stressed and mis‐stressed labels to the target objects; however, they were slower to fixate the target when hearing the mis‐stressed label. In Experiment 2, we examined whether infants appreciate that stress has a nonproductive role in English (i.e., altering the stress of a word does not typically signal a change in word meaning) by presenting infants with a familiar object paired with a novel object while hearing either correctly stressed or mis‐stressed familiar words (Experiment 2). Here, infants mapped the correctly stressed label to the familiar object but did not map the mis‐stressed label reliably to either the target or distractor objects. These findings suggest that word stress impacts the processing of familiar words, and infants have burgeoning knowledge that altering the stress pattern of a familiar word does not reliably signal a new referent.